2022
DOI: 10.3389/fmicb.2022.870316
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Hedgehog Signaling in Viral Infections

Abstract: The hedgehog (HH) signaling pathway is one of the key pathways that is indispensable for many developmental processes and postnatal tissue homeostasis. Dysregulated HH signaling could lead to developmental disorders and tumorigenesis in a variety of tissues via inherited or sporadic mutation, gene overexpression, and crosstalk with other signaling pathways. Recently, accumulating evidence has shown that HH signaling is targeted by viruses to facilitate viral transcription, immune evasion, and uncontrolled grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…7. The role of the Hh pathway in cancer and developmental disorders is well known [54,[61][62][63][64] , but involvement of the Hh pathway in infectious diseases is less studied [64][65][66] .…”
Section: Enrichment Analysis 3311 Enrichment Analysis For Proteins As...mentioning
confidence: 99%
See 1 more Smart Citation
“…7. The role of the Hh pathway in cancer and developmental disorders is well known [54,[61][62][63][64] , but involvement of the Hh pathway in infectious diseases is less studied [64][65][66] .…”
Section: Enrichment Analysis 3311 Enrichment Analysis For Proteins As...mentioning
confidence: 99%
“…7). Hepatitis B Virus (HBV), Hepatitis C Virus (HCV), Epstein-Barr Virus (EBV), Human PapillomaVirus (HPV), Human Immunodeficiency Virus (HIV), Human T-cell Leukemia Virus type I (HTLV-1), Influenza A Virus (IAV), and Kaposi's Sarcoma-associated HerpesVirus (KSHV) are known to induce pathological processes by regulating the expression, protein stability, and subcellular localization of Hh pathway components [64,65] . For instance, the hepatitis B pathway has the highest number of nodes shared with Hh-interacting proteins (Fig.…”
Section: Enrichment Analysis 3311 Enrichment Analysis For Proteins As...mentioning
confidence: 99%
“…However, this mechanism might be disturbed by KSHV infection, which utilizes the host PDGF receptor (PDGFR) and generates tumorigenesis [ 157 ]. Moreover, it is well known that HBV and HCV are involved in the activation of HH signaling in hepatocellular carcinoma (HCC), what contributes to several processes related strictly to HCC tumorigenesis like EMT, maintenance of CSCs, metastasis, and resistance to therapy [ 158 ]. Some authors revealed the aberration of HH signaling by HCV in liver fibrosis and HCC but also proposed the possibility of HH inhibitors as a potential target in future therapy [ 159 , 160 ].…”
Section: The Hh Signaling and Viral Infectionsmentioning
confidence: 99%
“…Some authors revealed the aberration of HH signaling by HCV in liver fibrosis and HCC but also proposed the possibility of HH inhibitors as a potential target in future therapy [ 159 , 160 ]. Researchers are still investigating the relationship between HCV and HH signaling components to establish the role of both factors in the pathogenesis of HCC [ 158 ]. The association between the HH signaling pathway and HPV/E6 protein was confirmed in the murine model of cervical cancer [ 161 ].…”
Section: The Hh Signaling and Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation